2018
DOI: 10.5114/wiitm.2018.77706
|View full text |Cite
|
Sign up to set email alerts
|

Lateral laparoscopic adrenalectomy in patients with previous abdominal surgery - single-center experience.

Abstract: IntroductionLateral transabdominal adrenalectomy (LTA) is the most common minimally invasive technique used to treat patients with adrenal tumors.AimTo analyze intra-operative and post-operative complications and reasons for conversion to open surgery in patients who underwent LTA and had previous abdominal surgery.Material and methodsFive hundred and nineteen patients underwent LTA in our center between 2005 and 2016. We identified a study group of 150 patients, with previous abdominal surgery. We analyzed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…It is widely documented in the literature that previous abdominal operations were not associated with surgery time of laparoscopic adrenalectomy [ 16 , 33 , 34 ], in agreement with our series.…”
Section: Discussionsupporting
confidence: 93%
“…It is widely documented in the literature that previous abdominal operations were not associated with surgery time of laparoscopic adrenalectomy [ 16 , 33 , 34 ], in agreement with our series.…”
Section: Discussionsupporting
confidence: 93%
“…In case of a close proximity of the pancreatic tail LUS enables to find the correct plane of dissection. LUS is extremely useful in patients after previous upper abdominal surgery when the anatomical planes may be changed but some authors do not find any significant association between previous surgery and conversion rate and we also did not find such significant correlation (1,30). LUS is non-invasive and non-irradiating, can be performed before, during and after dissection and repeated as many times as needed without negative impact on the patient and operating staff (31).…”
Section: Discussionmentioning
confidence: 63%
“…But they also reported increased operative time, intra-operative blood loss, and hospital LOS with large lesions [32]. Toutounchi et al, in their series, evaluated patients undergoing lateral laparoscopic adrenalectomy with previous abdominal surgery, and reported that the size of the tumor was a reason for conversion [33]. In our series, intraoperative blood loss, rate of conversion and hospital stay were similar between groups (p = 0.23, p = 0.18 and p = 0.07 respectively).…”
Section: Discussionmentioning
confidence: 99%